A Comparative Study Between the Law of Evidence Used in the Syariah Court And the Civil Court in Malaysia in the Context of Methods of Proof and Shariah Law: (Kaedah Pembuktian dalam Undang-undang Keterangan Mahkamah Syariah dan Mahkamah Sivil di Malaysia: Suatu Kajian Perbandingan) (Kanun: Jurnal Undang-undang Malaysia, 2019)
The focus of this study is to examine the similarities and differences between the Syariah Court Evidence (Federal Territories) Act 1997 (Act 561) and the Evidence Act 1950 (Act 56) which is applied in civil courts in the context of the methods of proving, and to study comparatively the implications as a result of adaptation and harmonisation. The study adopts a qualitative approach by analysing the provisions of relevant laws and is supplemented by interviews. The findings show that Act 561 provides for seven methods of proving, while five are adapted from Act 56. The findings also indicate that the use of qarinah (circumstancial evidence) in the Syariah Court Evidence Act differs from the methods of proving in syarak (Islamic law). Where evidence is concerned, the adaptation and Islamization of enactments has resulted in several issues that need to be addressed and fine-tuned in order to be comprehensive and complete references for application in the Syariah Courts, especially concerning methods of proving.Keywords: proving, methods of proving, Syariah Court Evidence Enactment, Evidence Act 1950.